2014
DOI: 10.1007/s00436-014-4187-z
|View full text |Cite
|
Sign up to set email alerts
|

Sealworm (Pseudoterranova decipiens) infection in grey seals (Halichoerus grypus), cod (Gadus morhua) and shorthorn sculpin (Myoxocephalus scorpius) in the Baltic Sea

Abstract: Access to the published version may require journal subscription. Published with permission from: Springer Verlag.Standard set statement from the publisher:"The final publication is available at Springer via http://dx.doi.org/ 10.1007/s00436-014-4187-z" Epsilon Open Archive http://epsilon.slu.se or some other variable which correlates with salinity, limits the distribution in the northern part. Sealworm (Pseudoterranova decipiens) infection in grey seals (Halichoerus grypus), cod (Gadus 30Keywords: Baltic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
(12 reference statements)
1
26
0
Order By: Relevance
“…These crustaceans become infected when they feed on nematode larvae released from the parasite eggs delivered by seal. A dominance of adult C. osculatum in Baltic grey seal stomachs was previously documented by Skrzypczak et al (2014) and Lunneryd et al (2015), and the increase of fish infections during the last decades may be caused by the rapidly expanding grey seal population (Haarder et al 2014). Several fish species are able to obtain infection when ingesting the first intermediate hosts, and the present field study documented that more than 10% of the Baltic sprat investigated was infected by up to 8 parasite larvae per fish, which is a higher infection level than previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These crustaceans become infected when they feed on nematode larvae released from the parasite eggs delivered by seal. A dominance of adult C. osculatum in Baltic grey seal stomachs was previously documented by Skrzypczak et al (2014) and Lunneryd et al (2015), and the increase of fish infections during the last decades may be caused by the rapidly expanding grey seal population (Haarder et al 2014). Several fish species are able to obtain infection when ingesting the first intermediate hosts, and the present field study documented that more than 10% of the Baltic sprat investigated was infected by up to 8 parasite larvae per fish, which is a higher infection level than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…This development has been noted during a period with a marked increase of the grey seal Halichoerus grypus population (Haarder et al 2014). These pinnipeds are final hosts for both C. osculatum and P. decipiens (Marcogliese et al 1996, McClelland 2002, Mattiucci & Nascetti 2008, Skrzypczak et al 2014, Lunneryd et al 2015. Eero et al (2015) suggested that heavy C. osculatum liver infections may partly explain the distress of the eastern population of Baltic cod, where juveniles (< 30 cm total length [TL]) perform successfully but larger cod (> 38 cm TL) show increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Some pathogens, particularly parasites with a free-living larval stage, possess some movement capabilities. For example, several species of parasitic nematodes (a phylum of generally parasitic round worms) have a free swimming larval stage and several intermediate hosts before ultimately infecting marine mammals or, in some cases, humans (Lunneryd et al 2015). Sea lice, an ectoparasite of commercially and ecologically important fish species (Jones et al 2006;Costello 2006), also possess a free-swimming larval stage, that influences their horizontal dispersal abilities (North et al 2008;Johnsen et al 2016); however, they are still largely dependent on local hydrodynamics for large scale (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The infection intensity has increased in Baltic Sea cod during the past 30 years, probably due to the increase of the population of grey seals ( Halichoerus grypus ) [3436], that are the final host of these parasites.…”
Section: Introductionmentioning
confidence: 99%